2014
DOI: 10.1242/jcs.155523
|View full text |Cite
|
Sign up to set email alerts
|

Secreted fibroblast miR-34a induces tubular cell apoptosis in fibrotic kidney

Abstract: Tubular epithelial cell apoptosis contributes to tubulointerstitial fibrosis but its regulation remained unclear. Here, in fibrotic kidney induced by unilateral ureteral obstruction (UUO), we demonstrated that miR-34a was markedly up-regulated in tubulointerstitial spaces and microvesicles isolated from kidney. However, the increased miR-34a was not de novo synthesized by proximal tubular epithelial cells but by fibroblasts after incubated with TGF-β1. MiR-34a was markedly up-regulated in microvesicles isolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 37 publications
3
31
0
Order By: Relevance
“…Taken together, these results suggest that miR-214 plays a critical role in the development and progression of breast cancer. miRNAs are endogenous, single-stranded, non-coding RNAs which are approximately 22 nucleotides in length and may suppress the post-transcriptional expression of target genes and are consequently involved in the regulation of various cellular processes, e.g., cell apoptosis, differentiation, development and metastasis (9,18,19). Growing evidence has reinforced the fact that miRNAs are frequently deregulated and aberrantly expressed in certain types of cancer, by acting as either tumor suppressors (9,20) or oncogenes (21, 22), and that they play a central role in carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, these results suggest that miR-214 plays a critical role in the development and progression of breast cancer. miRNAs are endogenous, single-stranded, non-coding RNAs which are approximately 22 nucleotides in length and may suppress the post-transcriptional expression of target genes and are consequently involved in the regulation of various cellular processes, e.g., cell apoptosis, differentiation, development and metastasis (9,18,19). Growing evidence has reinforced the fact that miRNAs are frequently deregulated and aberrantly expressed in certain types of cancer, by acting as either tumor suppressors (9,20) or oncogenes (21, 22), and that they play a central role in carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we demonstrated that the dysregulation of miR-214 is involved in the mechanisms of BC cell invasion by targeting p53. miRNAs are known to be endogenous single-stranded noncoding RNAs consisting of approximately 22 nucleotides, which can suppress the post-transcriptional expression of target genes and have been demonstrated to promote or suppress different cellular processes, e.g., cell apoptosis, differentiation, development, metastasis and invasion (31)(32)(33)(34)). An increasing number of studies have reinforced the notion that miRNAs are frequently deregulated and aberrantly expressed in certain types of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, overexpressing miR-34a levels increased the profibrogenic activity of TGF-β1 in cardiac fibroblast, whereas inhibition miR-34a levels weakened the activity. Another study showed TGF-β1-treated fibroblasts produce microvesicles with high miR-34a level which are able to induce tubular cell apoptosis in fibrotic kidney (Zhou et al, 2014). Furthermore, microRNA profiling also indicates that miR-34a is upregulated in bleomycin-induced pulmonary fibrosis suggesting it could be also play an important role in lung fibrosis (Honeyman et al, 2013; Xie et al, 2011).…”
Section: Mir-34a and Normal Tissue Radiation-induced Toxicitymentioning
confidence: 99%